Online flowers and gifts shop / Chit Kwung See - Chit , Kwung See (2000)
With the tremendous growth of the Internet and the expansion of the World Wide Web, more and more information is being put on the Internet. The Internet creates a global marketplace that breaks the barrier of time, place and distance, within which conducts Electronic Commerce. E-Commerce is a system that includes not only those transactions that center on buying and selling good and services to directly generate revenue, but also those transactions that support customer service, or facilitating communications between business partners. This thesis describes a developed system to automate purchasing of goods online. The Online Flowers and Gifts Shop names 'My E-Florist' is an e-commerce site that promotes and sells various flowers and gifts on the Internet. The main objective of this project is to develop an attractive, interactive and user friendly online selling website. My E-Florist is divided into 2 mam sections: Customer Section and Administrator Section. Customer Section allows the Internet users to browse and make order on the available items. On the other hand, the Administrator Section includes the user interfaces for authorized online shop's administrators to maintain their database and others administrative tasks. This project will review the methods, technologies and development tools that are used to set up an Electronic Commerce site. At the end, this project will implement all the requirements into a real system and analysis the strengths and weaknesses of the system. It is hope that the major problems faced by current system in an organization can be solved through this project.